POWER RELATION ANALYSIS IN BOLLYWOOD MOVIE DREAM GIRL (2019) - Almira Adawiyah, Farhana (Universitas Negeri Surabaya, 2024)
This study applies Michel Foucault's power relation and Gayatri C. Spivak's subaltern theory to analyze the power dynamics and representation of subaltern voices in the 2019 Indian movie Dream Girl. The movie, directed by Raaj Shaandilyaa, depicts the complex power structures connected to gender and class in Indian culture. It follows Karamveer Singh, who adopts a female persona to work as a phone entertainer. This study employs a descriptive qualitative method to examine significant scenes and discussions, with the goal of determining how Karamveer's gender performance both challenges and intersects with subaltern concerns. The study evaluates how the movie portrays marginalized voices and identities by drawing on Spivak's definition of the subaltern and Foucault's theory of power as pervasive and interconnected. The results demonstrate that the Dream Girl movie highlights the challenges subaltern groups have in reclaiming agency within these power structures while also criticizing the rigidity of gender binaries. The movie illustrates how dominant cultural narratives filter and, in some situations, quiet marginalized voices and how power can be both repressive and constructive. This study contributes to the discussion of how popular movies can serve as platforms for marginalized voices to be represented and a site of resistance.